Polycyclic Aromatic N-Heterocycles (PANHs) from Naphthyl and Anthracenyl Amines and Diols - Gonzalez-Sanchis, Nerea; Perez-Quilez, Paula; Bellezza, Delia; Flor-Sanchez, Anna; Ballesteros, Rafael; Ballesteros-Garrido, Rafael (Synthesis, 2022)
Nitrogen-containing polyaromatic compounds have been prepared in one step by combining diols and anthracenyl or naphthyl amines via acceptorless dehydrogenative condensation with ZnO and Pt/Al2O3 as heterogeneous catalysts.
Keywords: acceptorless dehydrogenative condensation; amines; diols; heterocycles; heterogeneous catalysis; polyaromatics